Injury Epidemiology and Risk Factors in Female Kabaddi Athletes: Insights from Event PON XXI 2024 for Enhanced Prevention and Management - Munawar, Ahmad Al; Şen, Şenay; Azadi, Filli (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. This research examines injury patterns, prevalence, and management in female Kabaddi athletes from North Sumatra during the PON XXI 2024 competition, addressing a gap in sports medicine regarding the physiological challenges faced by women in this contact sport. Kabaddi's lack of research on female athletes contributes to a significant deficit in understanding its physiological impact on women. Materials and methods. The study utilized a quantitative descriptive design with 22 female national Kabaddi athletes from North Sumatra, employing structured surveys, clinical assessments, and systematic injury documentation for comprehensive athlete health evaluation. The methodology comprised pre-competition medical screenings, post-competition injury documentation, and follow-up on recovery and rehabilitation, utilizing advanced statistical methods including descriptive analysis, frequency distributions, and correlation investigations, with significance testing established at p < 0.05. Results. Findings indicated a 100% injury rate among participants, highlighting the extreme demands of competitive Kabaddi, with the most common injuries being muscular strains (36.4%), joint sprains (27.3%), contusions (18.2%), and other soft tissue injuries (18.2%). The severity profile revealed 45.5% of injuries were mild (Grade I), 36.4% moderate (Grade II), and 18.2% severe (Grade III), with significant correlations identified between training intensity and injury occurrence (p = 0.015), body composition and injury susceptibility (p = 0.025), and age and injury risk (p = 0.042). Injury distribution showed lower limb injuries at 54.5%, upper limb injuries at 27.3%, and trunk/core injuries at 18.2%, with primary injury mechanisms including direct contact trauma (45.5%), overextension (27.3%), rapid directional change (18.2%), and repetitive stress (9.1%). Rehabilitation outcomes indicated an 86.4% recovery success rate, although a 13.6% recurring injury rate emphasized the need for comprehensive athlete management strategies. Conclusions. This research challenges prevailing norms in sports medicine by promoting gender-specific injury prevention, personalized management, and thorough monitoring. The study offers crucial insights into the injury patterns of female Kabaddi athletes and advocates for tailored approaches to athlete health and performance. By examining the complex interactions among physiological factors, training demands, and injury mechanisms, the research establishes a comprehensive framework for enhancing athlete care, preventive measures, and long-term sustainability in high-intensity sports.